2003
DOI: 10.1080/00016350310005510
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic variables and coronary heart disease

Abstract: This cross-sectional study was designed to explore a possible association between endodontic disease variables and coronary heart disease (CHD). Dental infections are hypothesized to be linked to atherosclerosis and could be a cause of vascular changes crucial for the development of CHD. Most studies have focused on periodontal disease. To our knowledge, no one has specifically studied endodontic variables as risk factors for the development of CHD. In 1992-93, a representative sample (n = 1056) of women in Gö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 8 publications
4
80
1
4
Order By: Relevance
“…In a summary thesis from 2007 [58], Frisk mixed data from the above mentioned 2003 study [47] with the results of 2 epidemiological studies on apical periodontitis in the Swedish population [56,57]. The objectives of this thesis were to further clarify clinical and socioeconomic risk factors for apical periodontitis and to reconsider, in a larger population, the possible association between apical periodontitis and CHD.…”
Section: Apical Periodontitis (Endodontic Infection) and Chdmentioning
confidence: 97%
See 2 more Smart Citations
“…In a summary thesis from 2007 [58], Frisk mixed data from the above mentioned 2003 study [47] with the results of 2 epidemiological studies on apical periodontitis in the Swedish population [56,57]. The objectives of this thesis were to further clarify clinical and socioeconomic risk factors for apical periodontitis and to reconsider, in a larger population, the possible association between apical periodontitis and CHD.…”
Section: Apical Periodontitis (Endodontic Infection) and Chdmentioning
confidence: 97%
“…The issue has been addressed only recently and has produced mixed results, with studies in favor of a positive correlation between apical periodontitis and coronary risk [40,59], and other negative [47,58] or inconclusive [55]. Unfortunately, the necessary scientific rigorousness was not always applied for a better understanding of the relationship between the presence of periapical lesions and CV risk.…”
Section: Conclusion On the Correlation Between Apical Periodontitis mentioning
confidence: 98%
See 1 more Smart Citation
“…A cross-sectional study by Frisk et al reported no such relation between dental infections and CVD; however, they studied females and evaluated endodontic variables and CHD and periodontal variables were not studied (38).…”
Section: Immunopathogenesis and Histopathologymentioning
confidence: 99%
“…More recently, a number of studies have focused on tooth loss as a risk This paper was originally presented as a thesis by T. Kurahashi at the Graduate School of Tokyo Dental College. factor in general health conditions, such as cardiovascular disease and stroke 1,6,8,15,16,19,20,27,29,30,[35][36][37]51,59) , dementia 52) , diabetes mellitus 11,31,41,42,45,56,57) , hypertension 55) , and gastrointestinal cancer 1) . Taken together, this indicates the potential of number of PT as an indicator of oral and general health status which can be used for comparisons both domestically and internationally.…”
Section: Introductionmentioning
confidence: 99%